Politics of Godfatherism and its Implication on Socio-Economic and Political Development of Nigeria - Ahmed, Fatima; Alhaji Ali, Mustapha (American International Journal of Social Science Research, 2019)
In contemporary democracy politics of godfatherism has become a universal issue in the political development of many countries Nigeria inclusive. The paper studied the implication of politics of godfatherism on the socio-economic and political development of Nigeria. Certainly, the politics of godfatherism have entered every hook and crannies of the nation and have affected the political structure of the country. This paper is qualitative in nature; data were obtained from secondary sources where numerous articles, newspapers, magazines, books reports, and archives were systematically reviewed. In elucidating the topic under examination, the researcher used Elite theory. This theory was advocated by Vilfredo Pareto in 1935, the postulation of the theory is that elites are replaced by another group of elites, meaning that the majority are unavoidably governed by the minority. The study found that the politics of godfatherism has a negative impact on the socio-economic and political development of the nation by confining power in the hands of the few elites at the expense of the masses (electorates). This has affected the socio-economic and political development of the nation, and by extension led to inter-party and intra-party defections, decamping’s and conflicts among the party members. Therefore, the study recommends the implementation of the direct primary election in the selecting candidate into elective positions. In addition to that, INEC should make a law that will discourage money politics and should as well punish the culprit involved in such an illegal political act.